2012
DOI: 10.1021/la300482x
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneity, Modulus, and Viscoelasticity of Polyelectrolyte Multilayers by Nanoindentation: Refining the Buildup Mechanism

Abstract: Atomic force microscopy, AFM, and nanoindentation of polyelectrolyte multilayers, PEMUs, made from poly(diallyldimethylammonium), PDADMA, and poly(styrene sulfonate), PSS, provided new insight into their surface morphology and growth mechanism. A strong odd/even alternation of surface modulus revealed greater extrinsic (counterion-balanced) charge compensation for fully hydrated multilayers ending in the polycation, PDADMA. These swings in modulus indicate a much more asymmetric layer-by-layer growth mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 59 publications
10
92
1
Order By: Relevance
“…Furthermore, Oleh et al [103] pointed out that the water is asymmetrically distributed along the three-dimensional structure of the multilayers. This has been recently confirmed for Ghostine et al [113] and Lehaf et al [212] in (PDADMAC + PSS) n multilayers. They found that the last layer play a key role in the hydration of the multilayers.…”
Section: Water Content and Hydrationsupporting
confidence: 65%
“…Furthermore, Oleh et al [103] pointed out that the water is asymmetrically distributed along the three-dimensional structure of the multilayers. This has been recently confirmed for Ghostine et al [113] and Lehaf et al [212] in (PDADMAC + PSS) n multilayers. They found that the last layer play a key role in the hydration of the multilayers.…”
Section: Water Content and Hydrationsupporting
confidence: 65%
“…Accordingly, the film surface is expected to be more "soft" when CHI adsorbs because of the larger excess of small counterions than in the films terminated in PEC [8][9][10]. For the CHI terminated films, we found unusual decrease in the electro-optical effect value at high field strengths (compared to the films ending in PEC) despite larger effects are measured for these films at low fields (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Another strategy for stiffening the polyelectrolyte multilayer films is to modify their internal composition and structure. According to Schlenoff et al, the mechanical properties of the films are strongly influenced by the presence of counterions, which must ensure charge balance within the film [8][9][10]. Multilayer films with extrinsic charge are much softer since counterions break ion pair cross-links between oppositely charged polyelectrolyte pairs [9].…”
Section: Introductionmentioning
confidence: 99%
“…From a mechanical properties arguments, these should be well adhered because PSS-terminated surfaces are stiff, with modulii in the range of 10 MPa. 34 In addition, the thickness of the thinner (0.15 M) PEMU allows the stiff (plastic) substrate to enhance the effective modulus the cells detect considerably. Using the estimates of Mehrotra et al, 15 who studied the relationship among thickness, stiffness, and cells on PDADMA/PSS multilayers and provided a model for an effective modulus based on finite difference analysis, the thin PEMU ( Figure 1B) is well within the range for strong substrate influence.…”
Section: ■ Results and Discussionmentioning
confidence: 99%